Adenovirus-mediated over-expression of the cyclin/cyclin-dependent kinase inhibitor, p21 inhibits vascular smooth muscle cell proliferation and neointima formation in the rat carotid artery model of balloon angioplasty. - Chang, M W (1995)
Vascular smooth muscle cell (VSMC) proliferation after arterial injury is important in the pathogenesis of a number of vascular proliferative disorders, including atherosclerosis and restenosis after balloon angioplasty. Thus, a better understanding of the molecular mechanisms underlying VSMC proliferation in response to arterial injury would have important therapeutic implications for patients with atherosclerotic vascular disease. The p21 protein is a negative regulator of mammalian cell cycle progression that functions both by inhibiting cyclin dependent kinases (CDKs) required for the initiation of S phase, and by binding to and inhibiting the DNA polymerase delta co-factor, proliferating cell nuclear antigen (PCNA). In this report, we show that adenovirus-mediated over-expression of human p21 inhibits growth factor-stimulated VSMC proliferation in vitro by efficiently arresting VSMCs in the G1 phase of the cell cycle. This p21-associated cell cycle arrest is associated both with significant inhibition of the phosphorylation of the retinoblastoma gene product (Rb) and with the formation of complexes between p21 and PCNA in VSMCs. In addition, we demonstrate that localized arterial infection with a p21-encoding adenovirus at the time of balloon angioplasty significantly reduced neointimal hyperplasia in the rat carotid artery model of restenosis. Taken together, these studies demonstrate the important role of p21 in regulating Rb phosphorylation and cell cycle progression in VSMC, and suggest a novel cytostatic gene therapy approach for restenosis and related vascular proliferative disorders.